Neotropical bees of the genus Heriades Spinola, 1808 (Hymenoptera: Megachilidae: Osmiini) with description of nine new species - Rojas-Arias, Laura; Griswold, Terry; Hinojosa-Díaz, Ismael; Morrone, Juan J.; Barajas, Ricardo Ayala (Zootaxa, 2025)
Heriades is a genus of solitary bees of the family Megachilidae. It is a monophyletic group divided into eight subgenera, of which Neotrypetes is the only one distributed in the Americas. The revisions by Michener (1938) and by Griswold (1984) are the only ones known for Heriades in the region. An updated revision of Heriades for the Neotropical region, based on external morphology and male genitalia, is presented here. 15 species recognized for the genus, nine of which are new to science. The species are: Heriades amanda sp. nov., H. briceida sp. nov., H. viridiana sp. nov., H. danuncia sp. nov., H. cristina sp. nov., H. vulcanica sp. nov., H. nora sp. nov., H. mariana sp. nov., H. luisa. sp. nov., H. bruneri Titus, H. crucifera Cockerell, H. currani Michener, H. leavitti Crawford, H. micheneri Timberlake, and H. texana Michener. A new synonym is proposed, Heriades tayrona Gonzalez & Griswold as synonym of H. currani syn. nov. Diagnoses, descriptions, illustrations and distributional maps of the species are included, as well as identification keys for the group in the region.